2021
DOI: 10.1186/s12905-021-01487-y
|View full text |Cite
|
Sign up to set email alerts
|

Do women empowerment indicators predict receipt of quality antenatal care in Cameroon? Evidence from a nationwide survey

Abstract: Background World Health Organisation (WHO) recommends quality antenatal care (ANC) for all pregnant women, as one of the strategies for achieving targets 3.1 and 3.2 of the sustainable development goals. Maternal mortality ratio remains high in Cameroon (782 maternal deaths per 100,000 live births). Extant literature suggest a positive association between women empowerment indicators and maternal healthcare utilisation in general. In Cameroon, this association has not received scholarly attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 39 publications
5
13
0
Order By: Relevance
“…In 2019, Benova et al, analyzed DHS data from 10 LMICs’s, which showed that Rwanda’s current proportion of women receiving all ANC components is higher than Nigeria’s (6.7%), close to that of Democratic Republic of Congo (12.6%) and lower than that of Zambia (21.8%) [ 12 ]. However, the proportion is similar to that observed in a study based on Cameroon's most recent DHS data (13.5%) [ 26 ]. Although components such as having a blood sample taken, blood pressure measured, urine sample taken and receiving iron tablets/syrups were utilized by over 80% of the women (95.5%, 87.4%, 82.6% and 80.6% respectively), having at least two tetanus injections (33.6%) and receiving drugs for intestinal parasites (43%) were highly underutilized.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In 2019, Benova et al, analyzed DHS data from 10 LMICs’s, which showed that Rwanda’s current proportion of women receiving all ANC components is higher than Nigeria’s (6.7%), close to that of Democratic Republic of Congo (12.6%) and lower than that of Zambia (21.8%) [ 12 ]. However, the proportion is similar to that observed in a study based on Cameroon's most recent DHS data (13.5%) [ 26 ]. Although components such as having a blood sample taken, blood pressure measured, urine sample taken and receiving iron tablets/syrups were utilized by over 80% of the women (95.5%, 87.4%, 82.6% and 80.6% respectively), having at least two tetanus injections (33.6%) and receiving drugs for intestinal parasites (43%) were highly underutilized.…”
Section: Discussionsupporting
confidence: 87%
“…Women who obtain 4 or more ANC visits have more contact with healthcare providers which renders them more likely to receive extensive health education and the best possible care [ 45 , 46 ]. Invariably, 4 or more ANC attendance is an indication of a woman’s consciousness and commitment to her wellbeing in pregnancy [ 6 , 26 ]. Additionally, frequent contact between the skilled provider and the pregnant woman helps in the development of good rapport between the two, enhances women’s familiarity with the health system, builds trust and confidence in the services received [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research (Afulani, 2016;Agha & Tappis, 2016;Ameyaw et al, 2021;Carvajal-Aguirre et al, 2017;Mugo et al, 2020), we discovered that the number of children ever born, marital status, region, and wealth quintile were all related to the quality of care received. Wealth has been linked to timely ANC contact and a greater number of ANC contacts, both of which increase the likelihood of receiving a greater number of ANC components during pregnancy (Ahinkorah et al, 2021;Jiwani et al, 2020;Mugo et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, 28% of women received the full set of interventions, which is slightly higher than the 14% reported by Ameyaw et al. (2021) in the same setting when they examined the relationship between women’s empowerment indicators and receiving quality care during pregnancy.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation